Non-reversible heat-induced gelation of a biocompatible Fmoc-hexapeptide in water. Issue 15 (1st April 2020) - Wojciechowski, Jonathan P.; Martin, Adam D.; Du, Eric Y.; Garvey, Christopher J.; Nordon, Robert E.; Thordarson, Pall
Abstract : A biocompatible Fmoc-hexapeptide which forms hydrogels at physiological pH upon heating is reported. Abstract : Hydrogel materials which respond to changes in temperature are widely applicable for injectable drug delivery or tissue engineering applications. Here, we report the unsual heat-induced gelation behaviour of a low molecular weight gelator based on an Fmoc-hexapeptide, Fmoc-GFFRGD. We show that Fmoc-GFFRGD forms kinetically stable fibres when mixed with divalent cations ( e.g. Ca 2+ ). Gelation of the mixture occurs upon heating of the mixture which enables electrostatic screening by the divalent cations and hydrophobic collapse of the fibres to give a self-supporting hydrogel network that shows good biocompatibility with L929 fibroblast cells. This work highlights a unique mechanism to initiate heat-induced gelation which should find opportunities as a gelation trigger for injectable hydrogels or fundamental self-assembly applications.